Propolis as an alternative remedy for the treatment of subclinical mastitis in dairy cows - Mikniene, Zoja; Puska, Grazvydas; Liaudanskas, Mindaugas; Siugzdaite, Jurate; Kubiliene, Loreta; Rudejeviene, Jurate; Zvikas, Vaidotas; Sutkeviciene, Neringa; Ragazinskiene, Ona; Trumbeckaite, Sonata (Frontiers in Veterinary Science, 2026)
BackgroundSubclinical mastitis is a widespread condition in dairy cows, often treated with antibiotics. Due to rising antimicrobial resistance, natural alternatives like propolis are gaining interest.ObjectivesTo evaluate the antibacterial efficacy of 5 and 10% propolis alginate emulsions in cows with subclinical mastitis and assess their effects on milk quality and systemic biomarkers.MethodsTen dairy cows diagnosed with subclinical mastitis were divided into two treatment groups (5 and 10% propolis emulsions). Emulsions were administered intramammarily and orally for 5 days. Bacterial load in milk, milk composition, blood biochemical and immunological parameters, phenolic compound profiles, and antioxidant activity were analysed using standard microbiological and biochemical methods.ResultsThe 5% emulsion reduced bacterial load by 2.27 log CFU/ml, outperforming the 10% emulsion (0.89 log CFU/ml; p < 0.05). Significant changes were observed in hepatic enzymes (ALT, AST), electrolytes (Ca, Mg, P), and renal markers (creatinine, urea). Immunological shifts included an increase in lymphocytes (+21%) and a decrease in neutrophils (−30%) in the 5% group. Antioxidant capacity was confirmed, with the highest activity observed in CUPRAC and ABTS assays. Phenolic compounds, including p-coumaric acid and flavonoids, contributed to the bioactivity.ConclusionA 5% propolis alginate emulsion was more effective than the 10% formulation in reducing bacterial counts and improving immunological and biochemical profiles. These findings support propolis as a promising natural alternative for treating subclinical mastitis, warranting further investigation into optimal formulations and long-term safety.